The effect of Seed Priming with Salicylic Acid on the Activity of Antioxidant Enzymes and Fat Peroxidation in Deteriorated Seeds (Glycine max (L.) Merrill, William variety) - Roksana Nazari; soheil parsa; Reza Tavakkol Afshari; sohrab mahmodi (علوم و فناوری بذر ایران, 2020)
In order to investigate the effect of priming on the improvement of physiological indices of antioxidant enzymes in soybean seeds, a factorial experiment was conducted in a completely randomized design with three replications at the Seed Science and Technology Laboratory of Tehran University in 2017. The factors studied included two levels of deterioration (48 and 72 hours), three levels of salicylic acid (0, 300, 600 μM) and three times the salicylic acid application (before decay, post-fall, before and after deterioration). The traits measured included antioxidant enzymes (glutathione redactase, superoxide dismutase, catalase, peroxidase, ascorbate peroxidase, glutathione peroxidase, membrane peroxidation or malondialdehyde). The results showed that deterioration level increasing, decrease the antioxidant enzymes activity and increase membrane peroxidation and soybean seed priming with salicylic acid hormone restore the decayed seeds and increase the activity of antioxidant enzymes. The highest activity of ascorbate peroxidase activity was observed at 72 hours with the time of salicylic acid application before and after deterioration at a concentration of 300 μm and 6.98. Reduction of malondialdehyde leakage rate when combined with 300 μM concentration of salicylic acid Was observed at 1.45. The results also showed that the priming at the same time improves the chemical properties of the seeds in the deterioration.